Infectious stimuli promote malignant B-cell acute lymphoblastic leukemia in the absence of AID - Rodríguez-Hernández, Guillermo; Opitz, Friederike V.; Delgado, Pilar; Walter, Carolin; Álvarez-Prado, Ángel F.; González-Herrero, Inés; Auer, Franziska; Fischer, Ute; Janssen, Stefan; Bartenhagen, Christoph; Raboso-Gallego, Javier; Casado-García, Ana; et al. (Nature communications, 2019)
The prerequisite to prevent childhood B-cell acute lymphoblastic leukemia (B-ALL) is to decipher its etiology. The current model suggests that infection triggers B-ALL development through induction of activation-induced cytidine deaminase (AID; also known as AICDA) in precursor B-cells. This evidence has been largely acquired through the use of ex vivo functional studies. However, whether this mechanism governs native non-transplant B-ALL development is unknown. Here we show that, surprisingly, AID genetic deletion does not affect B-ALL development in Pax5-haploinsufficient mice prone to B-ALL upon natural infection exposure. We next test the effect of premature AID expression from earliest pro-B-cell stages in B-cell transformation. The generation of AID off-target mutagenic activity in precursor B-cells does not promote B-ALL. Likewise, known drivers of human B-ALL are not preferentially targeted by AID. Overall these results suggest that infections promote B-ALL through AID-independent mechanisms, providing evidence for a new model of childhood B-ALL development. Infection or chronic inflammation is a risk factor for childhood B-cell precursor acute lymphoblastic leukemia. Here, the authors show that the DNA editing enzyme AID is expressed in infected B cells but using genetic mouse models show that it does not contribute to leukemia pathogenesis.